The Analisis Hambatan Belajar Operasi Bilangan Bulat : Analisis Hambatan Belajar Operasi Bilangan Bulat (Studi Kasus Pada Kelas VII SMP Katolik ST Paulus Palangka Raya) - Sisilia Malau; Sugilar .; Yumiati . (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Palangka Raya, 2021)
This research discussed the obstacles of learning Mathematics experienced by VII grade students in the odd semester of the 2018/2019 academic year at SMP Katolik St Paulus Palangka Raya in learning integers operation. These difficulties could be based on the mistakes made by students in solving the problems given. The purpose of the study was an in-depth analysis of learning obstacles experienced by students, teachers’ learning methods in explaining integers, and student barriers to applying integers in future life. The approach used a qualitative study that emphasized the character of descriptive research. In accordance with the approach used in this study, the analysis used was inductive. The data collection technique was carried out by triangulation, namely a combination of written test, interview, and documentation studies. The results showed that the three subjects experienced learning obstacles, type 1 students did not understand the nature of integer operations, especially negative integers; type 2 students had difficulty in determining integer operation formula analysis, type 3 students were not able to operate the operation in problem solving. The three students are students at a low level who experience learning difficulties as seen from the acquisition of test scores which are always below average. The cause of learning obstacles is due to students experiencing memory weakness, lack of motivation and low interest in learning. Key Word: learning obstacles, learning integers operation, memory, motivation, interest